Investment Cooperation Agreement on Equity Crowdfunding Platform from the Perspective of Sharia Economic Law - Muhammad Irkham Firdaus; Muhammad Abdul Aziz; Daud Sukoco; Novan Fatchu Alafianta (AL- IKTISAB Journal of Islamic Economic Law, 2021)
Equity crowdfunding is a new innovation in finance, which is an external product of financial technology, by combining financial systems with information technology. Equity crowdfunding is a combination of investment business model with information technology, where meetings between investors and fund managers are conducted online through websites on this platform. Crowdfunding equity platform is now growing rapidly and is very popular among the community, due to some of the facilities offered by the platform organizers for service users. Therefore, further research needs to be done on this business practice, which covers all aspects of the mechanisms and systems on this platform. The purpose of this study is to determine the mechanisms and systems of all aspects of the investment cooperation agreement model applied on the equity crowdfunding platform. The intended aspects include the mechanism of agreement (contract), profit sharing system, user protection, stock trading mechanism, dispute resolution, risk management, and so on. Furthermore, it aims to determine its compliance with Islamic law and the positive laws that apply in Indonesia. Investment agreements on equity crowdfunding platform can be implemented in mudharabah agreement, meanwhile, the agreement between the crowdfunding service provider and the crowdfunding user can use the wakalah bil ujrah contract. The percentage to revenue ratio can use the profit and loss distribution system and the revenue distribution system according to the agreement. Equity crowdfunding platform should really pay attention to consumer protection in accordance with the provisions in accordance with POJK and hifdzul maal theory. In addition, it must carry out risk management to minimize the occurrence of losses for some parties, and create a dispute resolution mechanism in accordance with Islamic law and economic law.